Motivasi Perkawinan Endogami pada Komunitas Alawiyyin di Martapura Kabupaten Banjar - Sulaiman Kurdi, Fathurrahman Azhari Zainal Muttaqien (IAIN Antasari Banjarmasin, 2013)
Endogamy marriage in which Syarifah is prohibited to get married with ahwal men, has been a long habit since their forefatherâs age. This study sought to identify and locate the variables considered by Habib and syarifah to be the motivation and consequences of endogamy marriage. This study results in findings with the proposition : Maintaining equality ( kafaah ) of nasab glory, preserving lineage, and maintaining kinship. As a result of endogamy marriage in the Alawiyin community in Martapura are : In social life : 1 ) many syarifah women who are not married. 2 ) Marriage is not attended by the family . 3 ) Differentiation in family relationships.Â Secondly, the consequences in the cultural life : 1 ) The Nasab relationship is disconnected from the Prophet Muhammad SAW. 2 ) Not entitled to use the title of Habib or syarifah because it was linked to the fathers lineage.